2000
DOI: 10.1590/s0100-879x2000000900006
|View full text |Cite
|
Sign up to set email alerts
|

Eggplant (Solanum melongena) infusion has a modest and transitory effect on hypercholesterolemic subjects

Abstract: Eggplant (Solanum melongena) is consumed extensively in Brazil. It has been believed that infusion of a powdered preparation of the fruit may reduce serum cholesterol. However, there are few documented reports on its effects on cholesterol metabolism and its possible hypocholesterolemic effect has not been proved by well-controlled studies. The aim of the present study was to observe the effects of S. melongena on the serum cholesterol and triglycerides of 38 hypercholesterolemic human volunteers ingesting S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 23 publications
(20 reference statements)
1
29
0
7
Order By: Relevance
“…These results do not support the popular use of S. melongena extract as hypocholesterolemic agent. On the other hand, Guimarães et al 25 assessed S. melongena powder and found 15.09% protein, 1.42% lipids, 13.89% fibers, 0.22% calcium, and 0.31% phosphorus, and qualitative tests assessing composition showed positive results for the presence of polyphenols and saponins. These results are similar to those found in the present study regarding proteins and lipids (13.34 and 1.85%, respectively); however, far below with respect to fiber (39.19%, i.e., fiber concentration in EF was 2.8 times greater) and calcium concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…These results do not support the popular use of S. melongena extract as hypocholesterolemic agent. On the other hand, Guimarães et al 25 assessed S. melongena powder and found 15.09% protein, 1.42% lipids, 13.89% fibers, 0.22% calcium, and 0.31% phosphorus, and qualitative tests assessing composition showed positive results for the presence of polyphenols and saponins. These results are similar to those found in the present study regarding proteins and lipids (13.34 and 1.85%, respectively); however, far below with respect to fiber (39.19%, i.e., fiber concentration in EF was 2.8 times greater) and calcium concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…), mas também ao seu propagado efeito hipocolesterolêmico 24 . Outros componentes, como niacina, vitamina C, flavonóides e fibra, presentes na berinjela, também parecem exercer alterações benéficas sobre o metabolismo de lipídeos 16,13 .…”
Section: Introductionunclassified
“…This pilot experiment, however, comprised individuals with total cholesterol < 200 mg/dL and covered a period of observation of 3 weeks, which may not have been sufficient to analyze occasional effects of eggplant extract. In a study using a 2% eggplant infusion, Guimarães et al 10 reported a transient and modest effect of eggplant infusion on cholesterol levels, which did not differ from that observed with the usual diet for hypercholesterolemic individuals. The authors suggest that the lack of efficacy of eggplant could be explained by its low concentration in the infusion (2%); in the study by Ribeiro Jorge et al 8 , the eggplant concentration in the juice administered to the rabbits was 58%.…”
Section: Discussionmentioning
confidence: 88%